Perilaku Masyarakat Lanjut Usia dalam Pemanfaatan Posyandu di Kecamatan Pasan Minahasa Tenggara - Amelia Andrita Alika Rondo; Diana Vanda D. Doda; Jehosua S. V. Sinolungan; Wulan Pingkan Julia Kaunang; Eva Mariane Mantjoto; Lucia Ingrid Regina Lefrandt (Jurnal Pengabdian Ilmu Kesehatan, 2025)
This study aims to analyze the factors associated with the utilization of elderly health posts (posyandu lansia) in Pasan Subdistrict, Southeast Minahasa Regency. The research used a quantitative analytic method with a cross-sectional approach involving 300 elderly respondents selected through proportional random sampling. Data were collected through structured interviews using a validated questionnaire and analyzed using chi-square statistical tests. The results showed significant associations between the level of knowledge (p = 0.002), attitudes (p = 0.011), access to services (p = 0.021), family support (p = 0.003), and the role of health officers (p = 0.018) with posyandu utilization. Knowledge emerged as the most dominant factor influencing behavior. These findings support Green’s theory that predisposing, enabling, and reinforcing factors affect health behavior. The study recommends improving health literacy among the elderly, enhancing family involvement, and optimizing the role of health personnel to increase participation in posyandu services. Limitations of the study include its geographic focus and the use of quantitative design only.